Board interlocks and corporate performance among firms listed abroad - Peng, Mike; Mutlu, C.; Sauerwald, S.; Au, K.; Wang, D. (Emerald, 2015)
This paper aims to explore the interlock-performance relationship among mainland Chinese firms listed in Hong Kong by taking advantage of a relationship-intensive context whereby such a link is likely to be especially important. Although strategic networks such as interlocking directorates have been found to affect a number of strategic behaviors, the link connecting board interlocks and corporate performance has remained ambiguous., Considerable light has been shed on the strategic networks of firms whose shares are listed abroad, which have been under-studied despite their rising importance in the global economy. Design/methodology/approach - Data come from a particularly interesting historical period - the early 1990s prior to Hong Kong’s 1997 handover to China. Both quantitative and qualitative research have been used. Findings - Empirically, it was found that good performance in an earlier period helps draw outside directors in a later period, and that network centrality and certain types of interlocks help improve performance, albeit with varying degrees. Overall, our results answer the question whether strategic networks such as interlocks matter for corporate performance with a qualified “yes”. Originality/value - Taking advantage of a relationship-intensive context, this article explores the interlock-performance relationship among mainland Chinese firms listed in Hong Kong. Focus is.